Admixture and genetic relationships of Mexican Mestizos regarding Latin American and Caribbean populations based on 13 CODIS-STRs - Salazar Flores, J. (2015)
Short tandem repeats (STRs) of the combined DNA index system (CODIS) are probably the most employed markers for human identification purposes. STR databases generated to interpret DNA profiles are also helpful for anthropological purposes. In this work, we report admixture, population structure, and genetic relationships of Mexican Mestizos with respect to Latin American and Caribbean populations based on 13 CODIS-STRs. In addition, new STR population data were included from Tijuana, Baja California (Northwest, Mexico), which represents an interesting case of elevated genetic flow as a bordering city with the USA. Inter-population analyses included CODIS-STR data from 11 Mexican Mestizo, 12 Latin American and four Caribbean populations, in addition to European, Amerindian, and African genetic pools as ancestral references. We report allele frequencies and statistical parameters of forensic interest (PD, PE, Het, PIC, typical PI), for 15 STRs in Tijuana, Baja California. This Mexican border city was peculiar by the increase of African ancestry, and by presenting three STRs in Hardy–Weinberg disequilibrium, probably explained by recurrent gene flow. The Amerindian ancestry in Central and Southeast of Mexico was the greatest in Latin America (50.9–68.6%), only comparable with the North of Central America and Ecuador (48.8–56.4%), whereas the European ancestry was prevalent in South America (66.7–75%). The African ancestry in Mexico was the smallest (2.2–6.3%) in Latin America (≥2.6%), particularly regarding Brazil (21%), Honduras (62%), and the Caribbean (43.2–65.2%). CODIS-STRs allowed detecting significant population structure in Latin America based on greater presence of European, Amerindian, and African ancestries in Central/South America, Mexican Mestizos, and the Caribbean, respectively.